Ethics in Psychological Research and Publication: The Mocked Essentials: [Etika dalam Penelitian dan Publikasi Psikologi: Esensi yang Diremehkan] - Jony Eko Yulianto; Juneman Abraham; Siaputra, Ide Bagus (ANIMA Indonesian Psychological Journal, 2024)
In the realm of psychological research, ethics is paramount for upholding human dignity, adhering to the guiding principle of “do good and do no harm”. Researchers bear the responsibility of ensuring that participants are well-informed about the research process, their rights to withdraw, and the protection of their identity and data confidentiality. In the era of generative artificial intelligence (AI), it becomes increasingly crucial for researchers to recognize and avoid potential ethical deviations such as fabrication, falsification, conflicts of interest, and plagiarism. Regrettably, in Indonesia, formal ethical training often receives inadequate attention or is even perceived as a hindrance to research. Ethics should serve to maintain public trust in the value and validity of research. This editorial aims to provide practical principles, rather than stringent rules, to guide researchers. Special emphasis is placed on the importance of ethics beyond informed consent, including handling high-risk topics, utilizing confidential datasets, and engaging with vulnerable communities. The editorial elucidates the process of ethical clearance, outlines four major stages in research ethics, and offers seven recommendations pertaining to ethical fitness. This is to ensure theoretical contributions and adherence to high ethical standards in various research contexts. Etika dalam penelitian psikologi adalah kunci untuk melindungi martabat manusia, mengikuti prinsip “berbuat baik dan tidak menyakiti”. Peneliti bertanggung jawab memastikan peserta paham tentang proses penelitian, hak penarikan diri, serta kerahasiaan identitas dan data. Lebih lanjut, di era artificial intelligence (AI) generatif, makin penting bagi peneliti untuk mengenali dan menghindari potensi penyimpangan seperti fabrikasi, falsifikasi, konflik kepentingan, dan plagiarisme. Sayangnya, di Indonesia, pelatihan etika secara formal kurang diperhatikan atau bahkan sering dianggap menghambat penelitian. Etika seharusnya mempertahankan kepercayaan publik terhadap nilai dan validitas penelitian. Editorial ini bertujuan menyediakan prinsip praktis, bukan hanya aturan ketat, untuk membimbing peneliti. Ada penekanan khusus terkait pentingnya etika selain persetujuan partisipasi, termasuk dalam topik berisiko tinggi, penggunaan dataset rahasia, dan bekerja dengan komunitas rentan. Editorial juga menjelaskan proses klirens etik, menguraikan empat tahapan utama dalam etika penelitian, dan menyediakan tujuh rekomendasi terkait kelaikan etik. Hal ini untuk memastikan sumbangan teoretis dan kepatuhan terhadap standar etika tinggi dalam berbagai konteks penelitian.